PENGARUH PROGRAM LITERASI TERHADAP KARAKTER PESERTA DIDIK (STUDI KORELASIONAL DI SMAN 83 JAKARTA) - Anas Sufyan; Nabil (Almarhalah: Jurnal Pendidikan Islam, 2024)
This research is motivated by the fact that literacy programs can be determined by the characteristics of the students they have. Literacy as understood by Indonesians was originally reading books which were considered boring and only a few enjoyed using them. Seeing lots of texts and thick books is not interesting for the current generation of reading, especially for students. This research aims to find out how much influence the Literacy Program has in shaping the characteristics of students at SMAN 83 Jakarta. The method used in this research uses a quantitative correlation method. Using the Simple Random Sampling method, there were 68 students at SMA Negeri 83 Jakarta, and equipped with data collection techniques, observation, interviews, questionnaires, documentation. Meanwhile, the analysis uses the product moment correlation technique. The research results show that if you look at the Product Moment coefficient test, it produces "rxy" or "ro" of 0.50, while "rt" in the table is significant at 5% = 0.235 and at a significance level of 1% = 0.306. Thus it can be seen that "ro" > "rt" is both significant at 5% and 1%. So based on these results the Alternative Hypothesis (Ha) is accepted or approved and the Null Hypothesis (Ho) is rejected or not approved. Based on this research, it can be concluded that there is an influence of the literacy program in shaping the characteristics of students at SMA Negeri 83 Jakarta.